Phenotypic Characterization of Salmonella Typhimurium Isolates from Food-animals and Abattoir Drains in Buea, Cameroon - Akoachere, Jane-Francis TK; Tanih, Nicoline F; Ndip, Lucy M; Ndip, Roland N (Journal of Health, Population and Nutrition, 2009)
Salmonella spp. have been extensively incriminated worldwide as common causes of bacterial gastroenteritis in humans, with food-animals serving as important reservoirs. The study was aimed at investigating cattle and pigs slaughtered in Buea as reservoirs of Salmonella Typhimurium and the susceptibility of isolates to antibiotics. In total, 230 specimens (comprising 50 each from the rectum, ileum, and gall bladder of cattle; and 10 each from same anatomical sites of pigs and 50 from abattoir drains) were analyzed for Salmonella using the standard microbiological, biochemical and serological techniques. Antibiotic susceptibility of the isolates was determined by the Kirby-Bauer disc-diffusion test. The isolates were characterized into biotypes using the API 20E kit, and results were analyzed using the chi-square test. Seventy-five (32.6%) of the 230 specimens were positive for S. Typhimurium, with pigs and abattoir drains presenting the highest level of isolation (40%). Biochemical typing grouped the isolates into five biotypes. Biotype I was the most prevalent (30.6%) while biotype IV was the least prevalent (9.3%) and was absent in samples from pigs. Antibiotic susceptibility studies revealed 14 antibiotypes based on antibiotics used in the study. The predominant antibiotype AMXR DOXRCEFR was recorded in 13 (17.3%) of the isolates. Multidrug resistance (to four or more antibiotics) was recorded in 50.7% (38/75) of the isolates. The most active drugs were ciprofloxacin (98.6%), ofloxacin (93.3%), amikacin (90.6%), and gentamicin (84%). All the isolates (100%) were resistant to tetracycline and ampicillin. Cattle and pigs were found to be reservoirs of S. Typhimurium in the environment of Buea, Cameroon, implying that foods from these sources, if not properly handled, could serve as vehicles for its transmission to humans. J Health Popul Nutr 2009 Oct; 27(5):612-618